2004
DOI: 10.1536/jhj.45.153
|View full text |Cite
|
Sign up to set email alerts
|

A Patient With Bicuspid Aorta and Intercoronary Continuity A Rare Variant of Coronary Circulation

Abstract: SUMMARYBidirectional flow in patients with normal coronary arteries is an indicator of intercoronary continuity, a rare variant of coronary circulation, distinct from collaterals. The case of an 18 year old Turkish male with bicuspid aorta and intercoronary artery is reported and different aspects of this interesting entity are emphasized. (Jpn Heart J 2004; 45: 153-155) Key words: Coronary angiography, Coronary circulation, Coronary anomalies, Bidirectional flow BIDIRECTIONAL coronary flow is frequently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Arat-Ozkan et al reported one case among 12,674 angiograms [4]. The true incidence of this entity is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Arat-Ozkan et al reported one case among 12,674 angiograms [4]. The true incidence of this entity is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…In the largest angiographic review by Yamanaka and Hobbs, the incidence of this entity was reported to be 0.002 % among 126595 cases (7). Arat-Ozkan et al examined 12.674 coronary angiograhy records and reported one case with intercoronary communication (8). Abreu et al rewieved ten years angiography record of 9388 patients and identified two cases with intercoronary communication (4).…”
Section: Discussionmentioning
confidence: 99%
“…2 It commonly occurs in the presence of coronary narrowing and after bypass surgery. 3 The persistence of a fetal pattern of coronary circulation is the Keywords ► coronary artery disease ► coronary intervention ► myocardial infarction ► stent ► atherosclerosis ► acute coronary syndrome ► risk factors…”
Section: Discussionmentioning
confidence: 99%